2010
DOI: 10.4314/acsj.v15i2.54418
|View full text |Cite
|
Sign up to set email alerts
|

Potential male gametophyte competition among <i>camellia sinensis</i> genotypes in isolated biclonal seed orchards

Abstract: Male fertility of crop plants is a function of pollen production and viability. In breeding, it is a requirement that there be similar fertilities among breeding parents within seed orchards. An in-vitro germination method was used in this study to determine variation in pollen viability among eight tea (Camellia sinensis) genotypes, over three flowering seasons in four isolated biclonal seed orchards located at two sites. The effect of environmental conditions on pollen germination was also studied on two pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…The observations signify variability among the genotypes in the developmental stages at which stigma receptivity and anther dehiscence occurred and also in pollen viability that could result unequal reproductive success in the different genotypes. Muoki et al (2007) and Wachira and Kamunya (2005) have also reported differential success of pollen parents when crossed with known female parents in the Kenyan germplasm. Similar circumstances were experienced by Bezbaruah (1975b), Neog and Singh (2003) and Bezbaruah and Saikia (1977) and the authors stated that the genotypes having variable affinity to the different tea varieties: C. sinensis var.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The observations signify variability among the genotypes in the developmental stages at which stigma receptivity and anther dehiscence occurred and also in pollen viability that could result unequal reproductive success in the different genotypes. Muoki et al (2007) and Wachira and Kamunya (2005) have also reported differential success of pollen parents when crossed with known female parents in the Kenyan germplasm. Similar circumstances were experienced by Bezbaruah (1975b), Neog and Singh (2003) and Bezbaruah and Saikia (1977) and the authors stated that the genotypes having variable affinity to the different tea varieties: C. sinensis var.…”
Section: Discussionmentioning
confidence: 90%
“…Tea is identified as having Group III wet type stigma according to the classification by Helslop-Harrison and Shivanna (1977). Phenological studies of tea flowering and seed setting conducted in the Kenyan and Indian tea germplasm have revealed seasonal variability among the varieties (Bezbaruah 1975a;Neog and Singh 2003;Muoki et al 2007). Pollination biology of tea, specifically in relation to floral visitors and effective pollinator populations has been adequately dealt in a report by Wickramaratne and Vitarana (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, compared to in-vitro germination test the pollen staining tests overestimated the viability of pollen. In-vitro pollen germination is generally believed to provide more reliable estimate of pollen viability (Muoki et al, 2007). Additionally, both viability and in-vitro germinability tests together provided important insight into understanding about the pollen quality.…”
Section: Pollen Quality Testsmentioning
confidence: 99%
“…Additionally, both viability and in-vitro germinability tests together provided important insight into understanding about the pollen quality. Notably, disparities in pollen quality are evidenced for potential male gametophyte competition and unequal reproductive success among C. sinensis genotypes (Muoki et al, 2007). The paternal traits, that is, phenology of male organ and amount of pollen produced, and pollen grain traits, that is, germination percentage, germination time, pollen tube growth rate, and selective fertilization are the factors that determine the fitness of pollinizers (Muoki et al, 2007).…”
Section: Pollen Quality Testsmentioning
confidence: 99%
See 1 more Smart Citation